Student discipline under Act 174: some issues - Maharam, Nor Azila (Pejabat Penasihat Undang-Undang, 2015)
This article discusses student discipline issues in universities, highlighting the challenges of managing indiscipline in an era where students are increasingly aware of their legal rights. While some students are knowledgeable about laws and the Constitution, many lack legal literacy. Universities continue to emphasize discipline, yet new types of offences, including internet-related misconduct, are emerging. Some students unknowingly commit acts that violate university regulations due to environmental influence and peer pressure.